Congelamento inverso em um modelo de vidro de spin fermiônico - Berger, Isabela Correa (2012)
The present work studies the counterintuitive phenomenon of inverse transitions (IT). The IT are a class of phase transitions (reversible) in which the ordered phase appears at higher temperatures than the disordered one. Different models have been proposed to describe characteristics of IT. The goal of this work is just to propose a model of disordered interactions, which is able to present general characteristics of a inverse transition type, the inverse freezing (IF). The IF is a reversible transition from a paramagnetic phase (PM) to the spin glass order (SG) on heating. Within this context the van Hemmen SG model is analyzed in a fermionic formulation, in which the spin operators are written as a bilinear combination of fermionic creation and annihilation operators. In this model the random interactions Ji j introduce disorder and frustration, and the chemical potential m controls the average occupancy of fermions per site. The problem is analyzed for two different types of quenched disorders: bimodal (discrete) and gaussian (continuous). It is important to note that the disorder in the model analyzed here were treated without the use of the replica method and its complications. The results depend on the particular disorder. The behavior of the order parameters, entropy and occupation number are analyzed. Phase diagrams of temperature T versus chemical potential m can then be build. A reentrance transition is found for a certain range of m when the gaussian distribution is adopted. This reentrance transition is associated with the IF that occurs in a first-order transition from the paramagnetic to the spin glass phase when the temperature increases. On the other hand, models following disordered interactions of Sherrington-Kirkpatrick (SK) type suggest that the onset of IF can be a consequence of complex scenario for the free energy. In these models the replica method is used to treat the disorder and the solutions present this complex scenario. However, from the results obtained in present fermionic van Hemmen model, it can be concluded that the necessary conditions for a model exhibit IF are the combined effects of frustration and magnetic dilution (favoring states not interacting, controlled by m). Thus, the treatment of model presented in this work does not use the replica method or the complicated scenario of free energy and it is able to reproduces the characteristics of an inverse freezing. This is attributed to the presence of frustration and magnetic dilution. Keywords: Disorder. Quantum Spin Glass. Fermionic model. Inverse transitions